Building Consumer Trust in E-Commerce (Survey: Wiralodra University Students) - Hanifa Nur Fadilah (Penerbit Hellow Pustaka, 2023)
This study aims to analyze the influencing factors and strategies that can be used to build consumer trust in e-commerce. Through a comprehensive literature review, this study identifies factors such as transaction security, data privacy, display quality, and information quality as important elements in building consumer trust. In addition, strategies such as ability, benevolence, and integrity also play an important role in increasing consumer trust. By understanding the importance of consumer trust and implementing appropriate strategies, businesses can strengthen customer relationships, increase loyalty, and achieve sustainable growth in an increasingly competitive environment. The research method used in this study is library research. Data is collected through analyzing various literature sources, including academic journals, books, research reports, and electronic sources related to consumer trust in e-commerce. Through this method, the research can provide deep insight into the theoretical foundations and empirical findings that exist in the literature related to consumer trust in e-commerce. The results of this study reveal some significant findings related to building consumer trust in the context of e-commerce. In this study, factors such as transaction security, data privacy, display quality and information quality were identified as key elements that influence consumer trust.